Establishment of a venovenous extracorporeal membrane oxygenation in a rat model of acute respiratory distress syndrome. (January 2023) - Li, Yongnan; Huang, Jian; Zhang, Rongzhi; Wang, Shixiong; Cheng, Xingdong; Zhang, Pengbin; Zhai, Kerong; Wang, Wei; Liu, Debin; Gao, Bingren
Introduction: Venovenous extracorporeal membrane oxygenation (VV ECMO) is now considered a reasonable option to salvage acute respiratory distress syndrome (ARDS). However, we lack a rodent model for experimental studies. This study was undertaken to establish an animal model of VV ECMO in ARDS rats. Methods: A total of 18 Sprague-Dawley (SD) rats (350 ± 50 g) were used in this study. Using a rat model of oleic acid (OA)-induced ARDS, VV ECMO was established through cavoatrial cannulation of the right jugular vein for venous drainage and venous reinfusion with a specially designed three-cavity catheter. Continuous arterial pressure monitoring was implemented by using a catheter through cannulation of the right femoral artery. The central temperature was monitored with a rectal probe. Arterial blood gas monitoring was implemented by a blood gas analyzer at three-time points: at baseline, 1-hour (after OA modeling), and 3.5-hour (after VV ECMO support). Lung tissue and bronchoalveolar lavage fluid were harvested respectively for protein concentration and pulmonary histologic evaluation to confirm the alleviation of lung injury during VV ECMO. Results: Following ARDS induced by OA, ten rats were successfully established on VV ECMO without failure and survived the ECMO procedure. VV ECMO alleviated lung injury and restored adequate circulation for the return of lung function and oxygenation. VV ECMO was associated with decreased lung injury score, wet/dry weight ratio, and ﬂuid leakage into airspaces. Conclusion: We have established a reliable, economical, and functioning ARDS rat model of VV ECMO.